Метафора у сталих виразах французької мови - Корпан, Леся; Korpan, Lesya (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проаналізовано вживання метафори і, відповідно, процес метафоризації у сталих виразах. На основі прикладів із художніх творів розглянуто особливості функціонування фразем у різних контекстах. Досліджено природу походження сталих сполучень слів із погляду мотивації / немотивації вибору лексичних одиниць. The article deals with the use of metaphors and, consequently, the process of metaphor formation in the stable expressions in modern French. Syntactic analysis has showed that there were some semantic-syntactic restrictions dividing these types of expressions. Based on belles-lettres examples the peculiarities of functioning of phrasemes in different contexts have been discussed, in particular, in a context where a metaphorical formation is made within the expression itself, or in term of a broader realization a context of the metaphorical meaning. Since the common feature of metaphors and phraseme is image, it’s making the comparative analysis more difficult. We have attempted to confirm the non-universal criterion of the complete stability expressions. The nature of origin of stable combinations of words have been examined in terms of motivation / non- motivated of the choice of lexical units.
Metaphor in French Stable Expressions.
Keywords: метафора; сталий вираз (фразема); образ; метафоризація; мотивація / немотивація; metaphor; stable expression (phraseme); image; metaphorical formation; motivation / non- motivation